Diversity and Seasonal Variation in Spider Abundance from MirajTahsil, Sangli, Maharashtra - Bibhishan, Sarwade Asha; Annda, Kamble Nitin (Asian Journal of Biological and Life Sciences, 2017)
Arachnida is one of the largest and important order from class Insecta. Arachnids are found over terrestrial ecosystem, however some inhabit freshwater environments and marine environments also. They comprise over 100,000 of species, including spiders, scorpions, harvestmen, ticks, mites and solifuges. Spiders are the most familiar of the arachnids and the most recorded species found around 40,000.Study relates with diversity of spiders from some of the freshwater sites of the MirajTahsilin the period of January, 2011 to December, 2013. Among collected spiders, species were identified from different families. Seasonal variations showed quantitative difference among species. Numerical data recorded was maximum in summer and rainy season as compared to winter. Physicochemical alterations has greatly influenced on the biodiversity at the selected sites.
Keywords: Miraj Tahsil; Physicochemical alteration; Spider diversity